Building a transformative agenda for accountability in SRHR: lessons learned from SRHR and accountability literatures. Issue 2 (31st May 2019) - Boydell, Victoria; Schaaf, Marta; George, Asha; Brinkerhoff, Derick W; Van Belle, Sara; Khosla, Rajat
Abstract: Global strategies and commitments for sexual and reproductive health and rights (SRHR) underscore the need to strengthen rights-based accountability processes. Yet there are gaps between these ambitious SRHR rights frameworks and the constrained socio-political lived realities within which these frameworks are implemented. This paper addresses these gaps by reviewing the evidence on the dynamics and concerns related to operationalising accountability in the context of SRHR. It is based on a secondary analysis of a systematic review that examined the published evidence on SRHR and accountability and also draws on the broader literature on accountability for health. Key themes include the political and ideological context, enhancing community voice and health system responsiveness, and recognising the complexity of health systems. While there is a range of accountability relationships that can be leveraged in the health system, the characteristics specific to SRHR need to be considered as they colour the capabilities and conditions in which accountability efforts occur.